Guernsey : Financial Sector Assessment Program Update-Technical Note on Stress Testing; Banking and Insurance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Stress testing (ST) was undertaken as part of the Guernsey Financial sector assessment Program (FSAP) Update in order to assess the resilience of the Guernsey financial system to a variety of potential strains. The approach taken was a simulation of the effect of a potential double-dip recession on solvency of Guernsey banks and insurance companies. The STs assess the sensitivity of banks and insurance companies to single-factor shocks to risk types affecting solvency and liquidity position of institutions. The mission recommends that future STs should be risk-based and that macroprudential analysis should be run on a regular basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet